Electrical, optical and structural properties of transparent conducting Al doped ZnO (AZO) deposited by sol-gel spin coating - Kaniz Naila Tonny; Rosaleena Rafique; Afrina Sharmin; Muhammad Shahriar Bashar; Zahid Hasan Mahmood (AIP Advances, 2018)
Al doped ZnO (AZO) films are fabricated by using sol-gel spin coating method and changes in electrical, optical and structural properties due to variation in film thickness is studied. AZO films provide c-axis orientation along the (002) plane and peak sharpness increased with film thickness is evident from XRD analysis. Conductivity (σ) of AZO films has increased from 2.34 (Siemens/cm) to 20156.27 (Siemens/cm) whereas sheet resistance (Rsh) decreases from 606300 (ohms/sq.) to 2.08 (ohm/sq.) with increase of film thickness from 296 nm to 1030 nm. Optical transmittance (T%) of AZO films is decreased from around 82% to 62% in the visible region. And grain size (D) of AZO thin films has been found to increase from 19.59 nm to 25.25 nm with increase of film thickness. Figure of Merit is also calculated for prepared sample of AZO. Among these four sample of AZO thin films, L-15 sample (having thickness in 895 nm) has provided highest figure of merit which is 5.49*10^-4 (Ω-1).